WAYS TO IMPROVE THE EFFECTIVENESS OF PERIODONTITIS TREATMENT IN DENTISTRY - Kholmirzaev Saidzhamol Akbarzhanovich (Web of Journals Publishing, 2025)
This article examines the treatment of periodontitis, the importance of professional hygiene and the necessary medications, as well as methods for eliminating pathogenic flora in periodontal pockets and reducing inflammation.
Keywords: Treatment, complication, effective method, periodontitis, surgical treatment, disease, periodontal pockets.